A survey on stateful data plane in software defined networks - Zhang, Xiaoquan; Cui, Lin; Wei, Kaimin; Tso, Fung Po; Ji, Yangyang; Jia, Weijia (Computer networks (Amsterdam, Netherlands : 1999), 2021)
Software Defined Networking (SDN), which decouples control plane and data plane, normally stores states on controllers to provide flexible programmability and convenient management. However, recent studies have shown that such configuration may cause frequent and unnecessary interactions between data plane and controllers in some cases. For example, a DDoS detection installed on a controller needs to fetch information from data plane periodically, introducing additional network delay and controller overhead. Thus, stateful data plane is proposed to offload states and operation logics from controller to data plane. Stateful data plane allows switches to perform some operations independently, accelerating packets processing while reducing overhead on both controllers and networks. However, stateful data plane increases the complexity of network devices and imposes many new challenges to the management and schedule of SDN enabled networks. This paper conducts a comprehensive survey on the latest research works and provides insights into stateful data plane. Both stateful data plane platforms and compilers are extensively summarized and analyzed, as well as explicit design of applications based on them. Afterwards, we dwell on the fundamental technologies and research challenges, including implementation considerations of stateful data plane. Finally, we conclude this survey paper with some future works and discuss open research issues.